Coating liquid for PET optical film coating and preparation method thereof

By applying a coating liquid containing components such as polyurethane acrylic resin, N-hydroxymethylacrylamide on the PET optical film, the problem of poor performance in scratch resistance and weather resistance is solved, and a coating with high adhesion, weather resistance and scratch resistance is achieved, and it is suitable for display screen protection layer and automotive glass.

CN119799152APending Publication Date: 2025-04-11BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510022923.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing PET optical films have poor performance in scratch resistance and weather resistance, and are difficult to meet the high requirements in the fields of display screen protection and automotive glass.

Method used

A coating liquid for PET optical film coating is adopted, including polyurethane acrylic resin, N-hydroxymethylacrylamide, coupling agent, photoinitiator, modified nanotitanium dioxide, ultraviolet absorber and active diluent. Through the synergistic action of these components, a coating with high adhesion, weather resistance and scratch resistance is formed.

Benefits of technology

It significantly enhances the surface hardness and scratch resistance of the PET optical film, while maintaining good light transmittance and weather resistance, and is suitable for display screen protection and automotive glass.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of PET optical film coatings, in particular to a coating liquid for a PET optical film coating and a preparation method of the coating liquid. The coating liquid for the PET optical film coating is prepared from the following preparation raw materials in parts by mass: 20 to 25 parts of polyurethane acrylic resin, 10 to 15 parts of N-hydroxymethyl acrylamide, 1 to 2 parts of a coupling agent, 4 to 6 parts of a photoinitiator, 8 to 10 parts of modified nano titanium dioxide, 0.2 to 0.3 part of an ultraviolet light absorber and 40 to 47 parts of a reactive diluent. The coating liquid for the PET optical film coating prepared by the invention is excellent in adhesive force, weather resistance, scratch resistance, light transmittance and the like, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PET optical film coatings, and in particular to a coating liquid for PET optical film coatings and a preparation method thereof. Background Art

[0002] PET film refers to polyethylene terephthalate material in the polyester family. It is a film made by biaxial stretching and other methods. PET film has the characteristics of high light transmittance, corrosion resistance, high temperature resistance, chemical properties and dimensional stability, and is suitable for outdoor product labels, packaging and optical film fields. The use of PET film is constantly expanding. At present, PET is one of the thermoplastic polyester materials with the largest output and the most widely used in the world. However, due to the low surface hardness and poor wear resistance of PET material, it needs to be coated with a wear-resistant protective coating to increase its service life.

[0003] In recent years, with the development of electronic display technology and the automotive industry, the requirements for PET optical films have been increasing, not only requiring good transparency and glossiness, but also higher requirements for scratch resistance and weather resistance. Although most PET optical films on the market currently improve these properties by coating one or more functional coatings on their surfaces, they still need to be improved to meet the application in display screen protection layers, automotive glass and other fields. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a coating liquid for PET optical film coating and a preparation method thereof. The coating liquid for PET optical film coating prepared in the present application has good adhesion, weather resistance and anti-scratch properties. Coating the functional coating on the PET optical film can enhance the surface hardness and achieve good anti-scratch performance. At the same time, it has good light transmittance and weather resistance, and is widely used in display screen protection layers, automotive glass and other fields.

[0005] In a first aspect, the present application provides a coating liquid for a PET optical film coating, which adopts the following technical solution: A coating liquid for PET optical film coating comprises the following raw materials by weight: 20-25 parts of polyurethane acrylic resin, 10-15 parts of N-hydroxymethyl acrylamide, 1-2 parts of coupling agent, 4-6 parts of photoinitiator, 8-10 parts of modified nano titanium dioxide, 0.2-0.3 parts of ultraviolet absorber and 40-47 parts of active diluent.

[0006] By adopting the above technical scheme, polyurethane acrylic resin: as the main film-forming substance, it provides the basic structure of the coating. Since it contains a considerable number of polyurethane bonds and a variety of functional bonds such as urea bonds, ether bonds, ester bonds, etc., it can form a coating with high wear resistance and elasticity after curing, and at the same time improve the adhesion between the coating and the PET substrate, so that the coating is more firmly attached to the substrate. N-hydroxymethyl acrylamide: this is a functional monomer that can participate in free radical polymerization under UV light irradiation, increase the cross-linking density of the coating, and thus enhance the hardness and solvent resistance of the coating. Coupling agent: used to improve the compatibility between inorganic fillers (such as modified nano titanium dioxide) and organic resins, promote close bonding between the two, and thus improve the overall performance of the coating, such as adhesion and weather resistance. Photoinitiator: decomposes under UV light to produce free radicals, initiates the polymerization reaction of monomers and prepolymers, and is a key component for coating curing. By controlling the amount of photoinitiator, the curing speed and depth of the coating can be adjusted. Modified nano titanium dioxide: The modified nano titanium dioxide not only has excellent UV shielding ability, but also can significantly improve the hardness and wear resistance of the coating. The modified nano titanium dioxide is more evenly distributed in the coating, which enhances the transparency and weather resistance of the coating. Ultraviolet absorber: It is used to absorb harmful ultraviolet rays, prevent ultraviolet rays from damaging the coating and substrate, and further improve the weather resistance and service life of the coating. Reactive diluent: The main function is to reduce the viscosity of the system and facilitate the construction of the coating liquid. At the same time, the active diluent itself also participates in the cross-linking reaction, increases the cross-linking density of the coating, and improves the comprehensive performance of the coating. Polyurethane acrylic resin and N-hydroxymethyl acrylamide: The two work together to form a highly cross-linked network structure through the initiation of UV photoinitiator, thereby improving the hardness, wear resistance and adhesion of the coating. Modified nano titanium dioxide and coupling agent: The modified nano titanium dioxide forms a stable interface with the polyurethane acrylic resin through the action of the coupling agent, which not only improves the transparency and weather resistance of the coating, but also enhances the hardness and wear resistance of the coating. The photoinitiator quickly decomposes under UV light to produce free radicals, which initiates the polymerization reaction; the active diluent reduces the viscosity of the system, making it easier to construct, and participates in the cross-linking reaction, further improving the performance of the coating. The UV absorber works synergistically with the modified nano-titanium dioxide to effectively block ultraviolet rays, protect the coating and substrate from damage by ultraviolet rays, and extend the service life of the coating. In summary, the various components cooperate with each other in the coating liquid for PET optical film coating to form a coating system with superior performance, which has good adhesion, weather resistance and anti-scratch properties, and is suitable for applications in display screen protection layers, automotive glass and other fields.

[0007] Preferably, the preparation method of the modified nano titanium dioxide comprises the following steps: S21. According to the mass fraction, 50 parts of nano-titanium dioxide are ultrasonically dispersed in an ethanol aqueous solution of 250 parts of ethanol and 50 parts of water, 4-6 parts of vinyltrimethoxysilane are added, the system temperature is set to 70-74° C., and stirred for 8-10 hours. After the reaction is completed, the solid sample is centrifuged, washed, and dried to obtain vinyltrimethoxysilane-modified nano-titanium dioxide; S22. Add 50 parts of vinyltrimethoxysilane-modified nano titanium dioxide to 200 parts of tetrahydrofuran by mass, disperse by ultrasonic, add 6 parts of 2,6-di-tert-butylphenol and 12 parts of sodium carbonate, mix well, increase the system temperature to 78-82°C, react for 6-8h, centrifuge the product to separate the solid sample, wash the solid sample with deionized water to neutrality, and finally dry in vacuum to obtain modified nano titanium dioxide.

[0008] By adopting the above technical scheme, the prepared modified nano titanium dioxide is modified by vinyl trimethoxysilane and 2,6-di-tert-butylphenol, which significantly improves its dispersibility and compatibility in the coating, thereby avoiding agglomeration and ensuring the uniformity and stability of the coating. The modified nano titanium dioxide has excellent UV shielding ability and antioxidant properties, and can effectively block harmful UV rays in PET optical film coatings, reduce light aging, and thus improve the light transmittance and weather resistance of the coating. The modified nano titanium dioxide has high hardness and wear resistance, and can significantly enhance the surface hardness of the PET optical film coating and improve its scratch resistance. The modified nano titanium dioxide synergizes with other components such as polyurethane acrylic resin, N-hydroxymethyl acrylamide, photoinitiator, etc., to further improve the comprehensive performance of the coating.

[0009] Preferably, the preparation method of the nano titanium dioxide is as follows: according to the mass fraction, 200 parts of ethanol and 30 parts of tetrabutyl titanate are added to a single-necked flask as a reaction liquid; 300 parts of ethanol, 10 parts of polyvinyl pyrrolidone K30 and 30 parts of distilled water are placed in a constant pressure dropping funnel and mixed evenly, and a small amount of hydrochloric acid is added to control the pH to 2.8-3.0 to obtain solution A; under ultrasonic stirring, solution A is slowly dripped into the reaction liquid at a speed of 2-3 seconds per drop, and the two are reacted at room temperature until the color of the system begins to turn blue, centrifugation, washing and drying are performed to obtain nano titanium dioxide with a particle size of 60-80 nanometers.

[0010] By adopting the above technical scheme, in the preparation process, through the steps of ultrasonic dispersion, reaction and centrifugal separation, the uniform dispersion and functional performance of the modified nano titanium dioxide can be ensured. At the same time, by adjusting the reaction conditions and the raw material ratio, the performance of the nano titanium dioxide can be further optimized, and the prepared nano titanium dioxide with a particle size of 60-80 nanometers and uniform particle size distribution has a strong ultraviolet shielding ability, can effectively absorb and reflect ultraviolet rays, and protect the optical film from damage by ultraviolet rays. It also has antioxidant properties and can resist the erosion of the optical film by oxidants in the environment. This is particularly important for application fields such as display screen protection layers and automotive glass.

[0011] Preferably, the coupling agent is composed of 3-isocyanatepropyltriethoxysilane, vinyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 4:3:4.

[0012] By adopting the above technical scheme, 3-isocyanatopropyltriethoxysilane: This compound can play a bridging role between the organic phase and the inorganic phase, and reacts with the hydroxyl group or other active hydrogen in the polyurethane acrylic resin through its isocyanate group to form a covalent bond, thereby improving the adhesion between the coating and the PET substrate. At the same time, its siloxane group can hydrolyze and condense at high temperature, further enhancing the durability and weather resistance of the coating. Vinyltrimethoxysilane: This component mainly participates in free radical polymerization through its vinyl group, cross-links with the polyurethane acrylic resin to form a three-dimensional network structure, thereby improving the mechanical strength and solvent resistance of the coating. In addition, its siloxane group can also react with the hydroxyl group on the surface of the substrate to enhance the adhesion of the coating. 3-aminopropyltriethoxysilane: The amino group of this compound can react with the functional group in the polyurethane acrylic resin to form a stable chemical bond, thereby improving the flexibility and adhesion of the coating. At the same time, its siloxane group can also react with the hydroxyl group on the surface of the substrate, further enhancing the durability and weather resistance of the coating. When these three components are mixed in a specific ratio, they can produce a significant synergistic effect, which is specifically manifested in the following aspects: 3-isocyanatopropyltriethoxysilane and 3-aminopropyltriethoxysilane react with the active groups on the surface of the substrate and in the resin through isocyanate and amino groups, respectively, to form a strong chemical bond, while vinyltrimethoxysilane further enhances the cohesion of the coating through free radical polymerization, thereby significantly improving the adhesion between the coating and the substrate. The siloxane groups of the three components can hydrolyze and condense at high temperatures to form Si-O-Si bonds, which have high stability and can effectively improve the weather resistance and durability of the coating. The three-dimensional network structure formed by the free radical polymerization of vinyltrimethoxysilane not only improves the mechanical strength of the coating, but also enhances the solvent resistance and scratch resistance of the coating. At the same time, the amino group of 3-aminopropyltriethoxysilane can introduce a flexible segment, so that the coating has a certain flexibility while maintaining high hardness, preventing the coating from cracking due to brittleness. In summary, these three coupling agents significantly improve the comprehensive performance of PET optical film coatings through their unique functional groups and synergistic effects, making it perform well in adhesion, weather resistance and scratch resistance.

[0013] Preferably, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxy-cyclohexyl phenyl ketone in a mass ratio of 2:3.

[0014] Preferably, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a mass ratio of 3:2.

[0015] By adopting the above technical scheme, dioctadecyl pentaerythritol phosphate can absorb ultraviolet rays in a wider wavelength range, prevent ultraviolet rays from damaging the coating, and improve the water resistance and chemical resistance of the coating. It has good thermal stability and chemical stability, can maintain stable performance at high temperatures, and is not easy to decompose. UV absorber UV-531 is a highly efficient ultraviolet absorber that can effectively absorb ultraviolet rays in a specific ultraviolet light band (such as UVA and UVB) and convert it into harmless heat energy release, thereby protecting the coating and substrate from damage by ultraviolet rays. It has high absorption efficiency and low yellowing, and can maintain good transparency and color stability under long-term exposure to ultraviolet rays. Dioctadecyl pentaerythritol phosphate and UV-531 are complementary in the ultraviolet absorption range. Dioctadecyl pentaerythritol phosphate covers a wider ultraviolet range, while UV-531 has high absorption capacity in a specific band. The combination of the two can achieve full-range protection against ultraviolet rays and improve the overall anti-ultraviolet performance of the coating. The high thermal stability and chemical stability of dioctadecyl pentaerythritol phosphate help protect UV-531 and prevent it from failing due to decomposition during long-term use, thereby extending the service life of the entire coating. In summary, dioctadecyl pentaerythritol phosphate and UV absorber UV-531 in the coating liquid for PET optical film coating not only improve the UV protection performance of the coating, but also enhance the stability and other comprehensive properties of the coating, so that the coating maintains excellent physical and optical properties during long-term use.

[0016] Preferably, the reactive diluent is composed of trimethylolpropane triacrylate and dipentaerythritol hexaacrylate in a mass ratio of 2:3.

[0017] Preferably, the polyurethane acrylic resin is an aliphatic polyurethane acrylic resin.

[0018] In a second aspect, the present application provides a method for preparing a coating liquid for a PET optical film coating, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned coating liquid for PET optical film coating, comprising the following steps: S91. In a high-speed dispersion reactor, add polyurethane acrylic resin, N-hydroxymethyl acrylamide and reactive diluent in order according to their weight fractions, raise the temperature to 55-60° C., stir for 30-40 minutes and then cool to room temperature to obtain solution A; S92. Add coupling agent, photoinitiator, modified nano titanium dioxide and ultraviolet absorber to solution A according to their mass fractions, and continue to stir and disperse for 20 minutes to obtain a coating solution for PET optical film coating.

[0019] In summary, the present application includes at least one of the following beneficial technical effects: 1. Good adhesion: The combination of polyurethane acrylic resin and N-hydroxymethyl acrylamide provides excellent adhesion, allowing the coating to adhere firmly to the PET optical film and not fall off easily.

[0020] 2. Excellent weather resistance: The addition of modified nano titanium dioxide and UV absorbers not only enhances the UV shielding ability of the coating, but also improves its antioxidant properties, thereby significantly improving the weather resistance of the coating, allowing it to maintain good performance even after long-term exposure to outdoor environments.

[0021] 3. Excellent anti-scratch performance: The modified nano titanium dioxide and various functional bonds in the polyurethane methacrylate system (such as polyurethane bonds, urea bonds, ether bonds, ester bonds, etc.) work together to make the coating have high surface hardness and wear resistance, effectively preventing scratches.

[0022] 4. High light transmittance: The addition of modified nano titanium dioxide not only improves the physical properties of the coating, but also increases its light transmittance, ensuring that the coating does not affect the transparency of the PET optical film while enhancing its protective performance.

[0023] 5. Excellent comprehensive performance: The use of active diluents reduces the viscosity of the system and increases the degree of cross-linking, so that the coating has the above advantages while also having good flexibility and feel, and is suitable for a variety of applications such as display screen protection layers and automotive glass. DETAILED DESCRIPTION

[0024] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] In the following examples and preparation examples, 1 part means 100 g.

[0026] Preparation Example 1 Preparation of modified nano titanium dioxide The preparation method of modified nano titanium dioxide comprises the following steps: S20, preparation of nano titanium dioxide, according to the mass fraction, add 200 parts of ethanol and 30 parts of tetrabutyl titanate into a single-necked flask as a reaction solution; separately place 300 parts of ethanol, 10 parts of polyvinyl pyrrolidone k30 and 30 parts of distilled water in a constant pressure dropping funnel and mix them evenly, and add a small amount of hydrochloric acid to control the pH to 2.9 to obtain solution A; under ultrasonic stirring, slowly drip solution A into the reaction solution at a speed of 2 seconds per drop, and react the two at room temperature until the color of the system begins to turn blue, centrifuge, wash and dry to obtain nano titanium dioxide with a particle size of 60-80 nanometers; S21. According to the mass fraction, 50 parts of nano-titanium dioxide with a particle size of 60-80 nanometers are ultrasonically dispersed in an ethanol-water solution of 250 parts of ethanol and 50 parts of water, 5 parts of vinyltrimethoxysilane are added, the system temperature is set to 73°C, and stirred for 9 hours. After the reaction is completed, the solid sample is centrifuged, washed, and dried to obtain vinyltrimethoxysilane-modified nano-titanium dioxide; S22. According to the mass fraction, 50 parts of nano-titanium dioxide modified by vinyltrimethoxysilane are added to 200 parts of tetrahydrofuran, ultrasonically dispersed, 6 parts of 2,6-di-tert-butylphenol and 12 parts of sodium carbonate are added, and after mixing, the system temperature is increased to 80°C, and the reaction is carried out for 7 hours. The solid sample is centrifuged from the product, and the solid sample is washed with deionized water to neutrality, and finally vacuum dried to obtain modified nano-titanium dioxide.

[0027] Preparation Example 2 Preparation of Nano-TiO2 In the preparation of nano titanium dioxide, 200 parts of ethanol and 30 parts of tetrabutyl titanate are added into a single-necked flask as a reaction liquid according to the mass fraction; 300 parts of ethanol, 10 parts of polyvinyl pyrrolidone K30 and 30 parts of distilled water are placed in a constant pressure dropping funnel and mixed evenly, and a small amount of hydrochloric acid is added to control the pH value to 2.9 to obtain solution A; under ultrasonic stirring, solution A is slowly dripped into the reaction liquid at a speed of 2 seconds per drop, and the two are reacted at room temperature until the color of the system begins to turn blue, centrifugation is performed, washing and drying are performed to obtain nano titanium dioxide with a particle size of 60-80 nanometers.

[0028] Example 1 A coating liquid for PET optical film coating, comprising the following raw materials by weight: 20 parts of aliphatic polyurethane acrylic resin, 10 parts of N-hydroxymethyl acrylamide, 1 part of coupling agent, 4 parts of photoinitiator, 8 parts of modified nano titanium dioxide, 0.2 parts of ultraviolet absorber, and 40 parts of active diluent, wherein the coupling agent is composed of 3-isocyanatopropyl triethoxysilane, vinyl trimethoxysilane and 3-aminopropyl triethoxysilane in a weight ratio of 4:3:4, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxy-cyclohexyl phenyl ketone in a weight ratio of 2:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a weight ratio of 3:2, and the active diluent is composed of trimethylolpropane triacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2:3; The method for preparing the coating liquid for the PET optical film coating comprises the following steps: S91. In a high-speed dispersion reactor, add aliphatic polyurethane acrylic resin, N-methylol acrylamide and reactive diluent in order according to their weight fractions, raise the temperature to 55° C., stir for 40 minutes and then cool to room temperature to obtain solution A; S92. Add coupling agent, photoinitiator, modified nano titanium dioxide and ultraviolet absorber to solution A according to their mass fractions, and continue to stir and disperse for 20 minutes to obtain a coating solution for PET optical film coating.

[0029] Example 2 A coating liquid for PET optical film coating, comprising the following raw materials by weight: 25 parts of aliphatic polyurethane acrylic resin, 15 parts of N-hydroxymethyl acrylamide, 2 parts of coupling agent, 6 parts of photoinitiator, 10 parts of modified nano titanium dioxide, 0.3 parts of ultraviolet absorber, and 47 parts of active diluent, wherein the coupling agent is composed of 3-isocyanatopropyl triethoxysilane, vinyl trimethoxysilane and 3-aminopropyl triethoxysilane in a weight ratio of 4:3:4, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxy-cyclohexyl phenyl ketone in a weight ratio of 2:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a weight ratio of 3:2, and the active diluent is composed of trimethylolpropane triacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2:3; The method for preparing the coating liquid for the PET optical film coating comprises the following steps: S91. In a high-speed dispersion reactor, add aliphatic polyurethane acrylic resin, N-methylol acrylamide and reactive diluent in order according to their weight fractions, raise the temperature to 60° C., stir for 30 minutes and then cool to room temperature to obtain solution A; S92. Add coupling agent, photoinitiator, modified nano titanium dioxide and ultraviolet absorber to solution A according to their mass fractions, and continue to stir and disperse for 20 minutes to obtain a coating solution for PET optical film coating.

[0030] Example 3 A coating liquid for PET optical film coating, comprising the following raw materials by weight: 22 parts of aliphatic polyurethane acrylic resin, 12 parts of N-hydroxymethyl acrylamide, 1.3 parts of coupling agent, 5 parts of photoinitiator, 9 parts of modified nano titanium dioxide, 0.25 parts of ultraviolet absorber, and 44 parts of active diluent, wherein the coupling agent is composed of 3-isocyanatopropyl triethoxysilane, vinyl trimethoxysilane and 3-aminopropyl triethoxysilane in a weight ratio of 4:3:4, the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxy-cyclohexyl phenyl ketone in a weight ratio of 2:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a weight ratio of 3:2, and the active diluent is composed of trimethylolpropane triacrylate and dipentaerythritol hexaacrylate in a weight ratio of 2:3; The method for preparing the coating liquid for the PET optical film coating comprises the following steps: S91. In a high-speed dispersion reactor, add aliphatic polyurethane acrylic resin, N-methylol acrylamide and reactive diluent in order according to their weight fractions, raise the temperature to 58° C., stir for 35 minutes and then cool to room temperature to obtain solution A; S92. Add coupling agent, photoinitiator, modified nano titanium dioxide and ultraviolet absorber to solution A according to their mass fractions, and continue to stir and disperse for 20 minutes to obtain a coating solution for PET optical film coating.

[0031] Comparative Example 1 The same as Example 3, except that an equal amount of the nano titanium dioxide prepared in Preparation Example 2 is used instead of the modified nano titanium dioxide.

[0032] Comparative Example 2 The same as Example 3, except that: the coupling agent is 3-isocyanatepropyltriethoxysilane.

[0033] Comparative Example 3 The same as Example 3, except that: the coupling agent is vinyltrimethoxysilane.

[0034] Comparative Example 4 The same as Example 3, except that: the coupling agent is 3-aminopropyltriethoxysilane.

[0035] Comparative Example 5 The same as Example 3, except that: the ultraviolet absorber is dioctadecyl pentaerythritol phosphate.

[0036] Comparative Example 6 The same as Example 3, except that: the ultraviolet absorber is ultraviolet absorber UV-531.

[0037] Performance testing The coating liquid samples for PET optical film coating prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 6 were respectively taken, and the coating was evenly coated on the PET optical film using an OSP-06 wire rod coater, and baked at 80°C for 25s; UV curing was carried out under an ultraviolet curing lamp, the UV curing time was about 18S, and the dry film thickness was controlled to be 4μm, to obtain a PET optical film with a coating, and the following tests were carried out. The results are shown in Table 1.

[0038] The test method used for scratch resistance is: the scratch resistance is characterized by the experimental method of critical load for scratches; during the test, sandpaper is placed on the surface of the film, a load of 0.200g is loaded on the sandpaper, and the sandpaper is pulled at a constant speed of about 10mm / s. The minimum mass for obvious scratches is used to represent the scratch resistance of the coating; Adhesion test standard is GB / T5210-1985; Light transmittance test: Tested in accordance with JIS K736 standard; Haze test: Tested in accordance with JIS K736 standard; Anti-UV performance: Refer to standard IEC TS62788-2, xenon lamp aging test 1500h test yellowing value.

[0039] Table 1 Performance test project Light transmittance / % Haze / % Adhesion Scratch resistance / g UV resistance Δb Example 1 92.8 0.8 Level 1 110 0.8 Example 2 93.7 0.6 Level 1 110 0.3 Example 3 95.1 0.3 Level 1 120 0.5 Comparative Example 1 85.4 2.5 Level 3 80 4.3 Comparative Example 2 91.8 1.1 Level 2 95 1.5 Comparative Example 3 92.3 0.8 Level 2 100 1.8 Comparative Example 4 92.6 0.9 Level 2 95 1.3 Comparative Example 5 93.1 0.7 Level 1 100 2.2 Comparative Example 6 92.6 0.9 Level 1 110 1.6 Analyzing the data in Table 1, we can see that: 1) The coating liquid for PET optical film coating prepared in Examples 1 to 3 has good adhesion, weather resistance and scratch resistance. Coating the functional coating on the PET optical film can enhance the surface hardness and achieve good scratch resistance. At the same time, it has good light transmittance and weather resistance, and is widely used in display screen protection layers, automotive glass and other fields.

[0040] 2) The comparative analysis of the performance of the coating liquid for PET optical film coating prepared in Example 3 and Comparative Example 1 shows that the prepared modified nano titanium dioxide is modified by vinyltrimethoxysilane and 2,6-di-tert-butylphenol, which significantly improves its dispersibility and compatibility in the coating, thereby avoiding agglomeration and ensuring the uniformity and stability of the coating. The modified nano titanium dioxide has excellent ultraviolet shielding ability and antioxidant properties, can effectively block harmful ultraviolet rays in the PET optical film coating, reduce light aging, and thus improve the light transmittance and weather resistance of the coating. The modified nano titanium dioxide has high hardness and wear resistance, can significantly enhance the surface hardness of the PET optical film coating, improve its scratch resistance, and improve the overall performance of the coating.

[0041] 3) The performance comparison analysis of the coating solution for PET optical film coating prepared in Example 3 and Comparative Examples 2-4 shows that the coupling agent is composed of 3-isocyanatopropyl triethoxysilane, vinyl trimethoxysilane and 3-aminopropyl triethoxysilane in a mass ratio of 4:3:4, and they can produce a significant synergistic effect, which is specifically manifested in the following aspects: 3-isocyanatopropyl triethoxysilane and 3-aminopropyl triethoxysilane react with the active groups on the surface of the substrate and in the resin through isocyanate and amino groups, respectively, to form a strong chemical bond, while vinyl trimethoxysilane further enhances the cohesion of the coating through free radical polymerization, thereby significantly improving the adhesion between the coating and the substrate. The siloxane groups of the three components can be hydrolyzed and condensed at high temperature to form Si-O-Si bonds, which have high stability and can effectively improve the weather resistance and durability of the coating. The three-dimensional network structure formed by the free radical polymerization reaction of vinyl trimethoxysilane not only improves the mechanical strength of the coating, but also enhances the solvent resistance and scratch resistance of the coating. At the same time, the amino group of 3-aminopropyl triethoxysilane can introduce flexible segments, so that the coating has a certain degree of flexibility while maintaining high hardness, preventing the coating from cracking due to brittleness. These three coupling agents significantly improve the comprehensive performance of PET optical film coatings through their unique functional groups and synergistic effects, making it perform well in adhesion, weather resistance and scratch resistance.

[0042] 4) A comparative analysis of the performance of the coating liquids for PET optical film coatings prepared in Example 3 and Comparative Examples 5-6 shows that the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a mass ratio of 3:2. The synergistic effect of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in the coating liquid for PET optical film coating not only improves the ultraviolet protection performance of the coating, but also enhances the stability and other comprehensive properties of the coating, so that the coating maintains excellent physical and optical properties during long-term use.

[0043] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A coating liquid for PET optical film coating, characterized in that: The preparation raw materials include the following by weight: 20-25 parts of polyurethane acrylic resin, 10-15 parts of N-hydroxymethyl acrylamide, 1-2 parts of coupling agent, 4-6 parts of photoinitiator, 8-10 parts of modified nano titanium dioxide, 0.2-0.3 parts of ultraviolet absorber and 40-47 parts of active diluent.

2. The coating liquid for PET optical film coating according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide comprises the following steps: S21. According to the mass fraction, 50 parts of nano-titanium dioxide are ultrasonically dispersed in an ethanol aqueous solution of 250 parts of ethanol and 50 parts of water, 4-6 parts of vinyltrimethoxysilane are added, the system temperature is set to 70-74° C., and stirred for 8-10 hours. After the reaction is completed, the solid sample is centrifuged, washed, and dried to obtain vinyltrimethoxysilane-modified nano-titanium dioxide; S22. Add 50 parts of vinyltrimethoxysilane-modified nano titanium dioxide to 200 parts of tetrahydrofuran by mass, disperse by ultrasonic, add 6 parts of 2,6-di-tert-butylphenol and 12 parts of sodium carbonate, mix well, increase the system temperature to 78-82°C, react for 6-8h, centrifuge the product to separate the solid sample, wash the solid sample with deionized water to neutrality, and finally dry in vacuum to obtain modified nano titanium dioxide.

3. The coating liquid for PET optical film coating according to claim 2, characterized in that: The preparation method of the nano titanium dioxide is as follows: according to the mass fraction, 200 parts of ethanol and 30 parts of tetrabutyl titanate are added into a single-necked flask as a reaction liquid; 300 parts of ethanol, 10 parts of polyvinyl pyrrolidone K30 and 30 parts of distilled water are placed in a constant pressure dropping funnel and mixed evenly, and a small amount of hydrochloric acid is added to control the pH value to 2.8-3.0 to obtain a solution A; under ultrasonic stirring, the solution A is slowly dripped into the reaction liquid at a speed of 2-3 seconds per drop, and the two are reacted at room temperature until the color of the system begins to turn blue, centrifugation is performed, washing and drying are performed to obtain nano titanium dioxide with a particle size of 60-80 nanometers.

4. The coating liquid for PET optical film coating according to claim 1, characterized in that: The coupling agent is composed of 3-isocyanatepropyltriethoxysilane, vinyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 4:3:

4.

5. The coating liquid for PET optical film coating according to claim 1, characterized in that: The photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxy-cyclohexyl phenyl ketone in a mass ratio of 2:

3.

6. The coating liquid for PET optical film coating according to claim 1, characterized in that: The ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and ultraviolet absorber UV-531 in a mass ratio of 3:

2.

7. The coating liquid for PET optical film coating according to claim 1, characterized in that: The active diluent is composed of trimethylolpropane triacrylate and dipentaerythritol hexaacrylate in a mass ratio of 2:

3.

8. The coating liquid for PET optical film coating according to claim 1, characterized in that: The polyurethane acrylic resin is an aliphatic polyurethane acrylic resin.

9. A method for preparing a coating liquid for a PET optical film coating as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S91. In a high-speed dispersion reactor, add polyurethane acrylic resin, N-hydroxymethyl acrylamide and reactive diluent in order according to their weight fractions, raise the temperature to 55-60° C., stir for 30-40 minutes and then cool to room temperature to obtain solution A; S92. Add coupling agent, photoinitiator, modified nano titanium dioxide and ultraviolet absorber to solution A according to their mass fractions, and continue to stir and disperse for 20 minutes to obtain a coating solution for PET optical film coating.

Citation Information

Cited By

  • Preparation process of PET (Polyethylene Terephthalate) film laser printing coating

    CN120173462A

  • High-haze high-temperature-resistant lower diffusion film and preparation method thereof

    CN120370447A

  • High-temperature-resistant waterproof PET label and preparation process thereof

    CN120564523A

  • Single coating type UV and heat dual-curing laser anti-counterfeiting coating and UV mold pressing microstructure copying process

    CN121930733A